Solo Naik Kelas: Strategi Integrasi Event Budaya, Olahraga, dan Ekonomi Kreatif untuk Penguatan Daya Saing Kota Surakarta - Karnalita Miftakhul Huda; Nafi’atul ‘Athiyah (Jurnal Bengawan Solo Pusat Kajian Penelitian dan Pengembangan Daerah Kota Surakarta, 2025)
The City of Surakarta is one of the regions in Indonesia with significant potential for the development of its cultural, creative economy, and sports sectors. These three sectors possess a strong appeal for both domestic and international tourists while contributing to the strengthening of the city’s identity. However, the short duration of tourist stays remains a major challenge that hinders the optimal development of Surakarta’s tourism sector. Most tourists only make brief visits without fully exploring the city’s rich and diverse potential. This study proposes an integrative strategy based on inter-departmental collaboration as a solution to extend tourists’ length of stay and enhance the quality of their travel experiences. Two main programs are introduced: the Solo Heritage Run and the City Tour Package. The Solo Heritage Run is a monthly weekend event that combines running activities with the promotion of local culture and culinary attractions, while the City Tour Package offers flexible and educational tour routes that can be enjoyed on any day. Both programs are designed synergistically to integrate educational, economic, and cultural elements into one cohesive experience. The study’s findings indicate that the implementation of these programs has the potential to enrich the qualitative value of tourism, increase the participation of local economic actors, and boost Regional Original Revenue (PAD). This research recommends a cross-sectoral approach as a strategic model for strengthening regional tourism competitiveness in a sustainable and inclusive manner.